Case studies in system of systems, enterprise systems, and complex systems engineering - Gorod, Alex, editor; White, Brian E., editor; Ireland, Vernon, editor; Gandhi, S. Jimmy, editor; Sauser, Brian, editor (Boca Raton : Taylor & Francis, 2014)
Includes bibliographical references and index